PENGGUNAAN MEDIA GAMBAR SIMBOL-SIMBOL PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PPKn PESERTA DIDIK KELAS 1 DI SDN SIWALAN - Lutfinisa, Nur Aini; Suyoto, Suyoto; Faiqoh, Elok; Listyarini, lkha (Universitas Muhammadiyah Tapanuli Selatan, 2024)
A good learning process is a driving factor for success in education. In the learning process students are required to be active so that learning is effective and interactive, but basically teachers are still focused on worksheet books and do not involve students and teachers do not use learning media, so that student learning outcomes are less than optimal. This research aims to determine the influence of media images of Pancasila symbols in improving PPKn learning outcomes for students at SDN Siwalan. This research uses a quantitative Pre-Experimental Design approach with the One Group Pretest Posttest type. The sample used was 27 grade 1 students at Siwalan Elementary School. The results of research that have been tested for normality in the pretest and posttest are normally distributed. Judging from the pretest results, the SPSS output has a value of 0.093 Î± (0.05), which means the data is normally distributed. From the SPSS output posttest results in the sig column. which has a value of 0.090 Î± (0.05) which means the data is normal. From the results of the paired sample t test, sig results were obtained. (2-tailed) 0.000. If sign. (2-tailed) 0.000 Î± (0.05) then Ha is accepted which means that there is an influence of the media of pictures of Pancasila symbols in improving the PPKn learning outcomes of class 1 students at SDN Siwalan and in the Normalized Gain test based on what has been done it is calculated using SPSS 26, the integration results are high.